Principles of RNA base pairing: structures and energies of the trans Watson-Crick/sugar edge base pairs - Sponer, Judit E; Spackova, Nad'a; Leszczynski, Jerzy; Sponer, Jirí (The journal of physical chemistry. B, 2005)
Due to the presence of the 2'-OH hydroxyl group of ribose, RNA molecules utilize an astonishing variability of base pairing patterns to build up their structures and perform the biological functions. Many of the key RNA base pairing families have no counterparts in DNA. In this study, the trans Watson-Crick/sugar edge (trans WC/SE) RNA base pair family has been characterized using quantum chemical and molecular mechanics calculations. Gas-phase optimized geometries from density functional theory (DFT) calculations and RIMP2 interaction energies are reported for the 10 crystallographically identified trans WC/SE base pairing patterns. Further, stable structures are predicted for all of the remaining six possible members of this family not seen in RNAs so far. Among these novel six base pairs, the computations substantially refine two structures suggested earlier based on simple isosteric considerations. For two additional trans WC/SE base pairs predicted in this study, no arrangement was suggested before. Thus, our study brings a complete set of trans WC/SE base pairing patterns. The present results are also contrasted with calculations reported recently for the cis WC/SE base pair family. The computed base pair sizes are in sound correlation with the X-ray data for all WC/SE pairing patterns including both their cis and trans isomers. This confirms that the isostericity of RNA base pairs, which is one of the key factors determining the RNA sequence conservation patterns, originates in the properties of the isolated base pairs. In contrast to the cis structures, however, the isosteric subgroups of the trans WC/SE family differ not only in their H-bonding patterns and steric dimensions but also in the intrinsic strength of the intermolecular interactions. The distribution of the total interaction energy over the sugar-base and base-base contributions is controlled by the cis-trans isomerism.
Keywords: chemické jevy; vodíková vazba; fyzikální chemie; Isomerism; isomerie; RNA; Chemistry, Physical; molekulární modely; Base Pairing; Crystallography, X-Ray; Carbohydrates; Chemical Phenomena; ribosa; Ribose; Hydrogen Bonding; sacharidy; krystalografie rentgenová; Models, Molecular; párování bází